Twitter as a Public Sphere for COVID-19 Vaccine Discussion - Nurhajati, Lestari; Wijayanto, Xenia Angelica; Fitriyani, Lamria Raya (CHANNEL: Jurnal Komunikasi, 2022)
This study aims to discover how Gen Z discusses the COVID-19 vaccine through social media discussion, participation, and ideas in a virtual public space. Recently, online media coverage has been massive, especially regarding the COVID-19 vaccine produced in Indonesia or purchased by the Indonesian government from foreign countries. Another thing that was also discussed was the priority of the vaccine recipients, which ministers in Indonesia presented with different approaches. Coordinating Minister for Human Development and Culture, Muhadjir Effendy, emphasized that lecturers and teachers are prioritized to receive vaccines. Previously, the coordinating minister for the Economy, Airlangga Hartarto, said medical personnel was prioritized. The Chief Executive of COVID-19 Handling and National Economic Recovery Committee (KPCPEN), Erick Thohir, also stated that health workers were a priority. Meanwhile, the Minister of Health, Terawan, noted that the priority for vaccine recipients is medic, paramedic, public services, TNI/Polri, and all educators. This variety of information and news is understood differently by the Indonesian people, including among Gen Z. Using the virtual public sphere, where freedom of expression in a democratic manner is the key to the emancipatory communication process. This research method uses extensive data analysis to collect conversations about the COVID-19 vaccine on social media, especially on Twitter, from 1-31 March 2021. The results show that although Generation Z is actively involved in the COVID-19 Vaccine discussion, they are not The Prominent Key Opinion Leader (KOL), who is the key player in communicating this issue via Twitter.